Trials of sovereignty : mercy, violence, and the making of criminal law in british india, 1857-1922 / Alastair McClure. - McClure, Alastair (Studies in legal history., 2024)
Trials of Sovereignty offers the first legal history of mercy and discretion in nineteenth and twentieth-century India. Through a study of large-scale amnesties, the prerogative powers of pardon, executive commutation, and judicial sentencing practices, Alastair McClure argues that discretion represented a vital facet of colonial rule. In a bloody penal order, officials and judges consistently offered reduced sentences and pardons for select subjects, encouraging others to approach state institutions and confer the colonial state with greater legitimacy. Mercy was always a contested expression of sovereign power that risked exposing colonial weakness. This vulnerability was gradually recognized by colonial subjects who deployed a range of legal and political strategies to interrogate state power and question the lofty promises of British colonial justice. By the early twentieth century, the decision to break the law and reject imperial overtures of mercy had developed into a crucial expression of anticolonial politics.